PROSPECTS FOR THE DEVELOPMENT OF FRUIT AND VEGETABLE ENTERPRISES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article is based on the importance of the fruit and vegetable industry in developed and developing countries. The opinions of scientists conducting research in this field are analyzed. Forms of fruit and vegetable growing and supplying enterprises operating in accordance with market relations have been proposed. The export potential of fruit and vegetable products is analyzed and conclusions are drawn.